Epidermolytic Hyperkeratosis - case report - Marcos Takeyoshi Hayashida; Grasiela Lissa Mitsui; Natalia Ivanoff dos Reis; Giovana Fantinato; Domingos Jordão Neto; Ana Maria da Cunha Mercante (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Epidermolytic hipercetarose is a rare genodermatosis, with a prevalence of 1:100.000 to 1:300.000, with autosomal dominant inheritance. We report the case of a 5 year old girlwho presented an hypertrophic verrucous plaques in the neck, under arm, buttocks, knees, pelvis, legs, dorsum of the right foot and elbows. Histological examination of the skin lesions showed typical changes of epidermolytic hyperkeratosis. Because it is an autosomal dominant disorder with complete penetrance, the individual carrying the mutation will necessarily develop the disease. However, in 50% of cases postzygotic mutation occur. The case report emphasizes early diagnosis and differential diagnoses with ichthyosis and other bullous diseases of childhood, as well as discussing the therapeutic possibilities.